IMPLEMENTASI NILAI DAN ETIKA PEKERJA SOSIAL DALAM PENANGANAN KLIEN KORBAN PENYALAHGUNAAN NAPZA DI CAMP ASSESMENT, YOGYAKARTA - Widodo, Ageng (KOMUNIKA, 2019)
This journal describes the implementation of values and ethics of social workers in handling drugabuse clients at Camp Assessment, Yogyakarta. Social workers as professionals in to do helpingmust be guided by values and ethics. The implementation of values and ethics of social workersapplied in the assessment camp includes several things. First, the service that prioritizes the goalto help people in need and focus on social problems. Secondly, social justice is notdistinguishing between rich and poor clients. Third, attaching importance to human relationsconsiders the client as a partner for effective and efficient treatment. Fourth, integrity andcompetence, as social workers must have the skills, knowledge, and values to do helping.However, in applying values and ethics, social workers experience a dilemma including anan imbalance between clients and social workers and then inadequate facilities.